2010
DOI: 10.1182/blood.v116.21.248.248
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Trial Results Following Administration of a Low Dose of a Novel Self Complementary Adeno-Associated Viral Vector Encoding Human Factor IX In Two Subjects with Severe Hemophilia B

Abstract: 248 We have developed a unique approach for the treatment of hemophilia B (HB) that is currently being tested in the clinic. This open-label Phase I/II clinical trial entails peripheral vein administration of a single dose of our novel self complementary AAV vector encoding a codon-optimised human FIX transgene (scAAV2/8-LP1-hFIXco) into adult subjects with severe HB. Our plan is to evaluate three dose levels, progressing to the intermediate and high doses only in the absence of toxicity in a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In a separate series of studies, self-complementary AAV8 containing human factor IX under the control of a synthetic liver-specific promoter was shown to establish prolonged high levels of gene expression when administered to mice and non-human primates [ 55 ]. This vector has been applied recently in a clinical trial where expression in one patient has risen from baseline to 1.5-2% and has maintained this level for more than 5 months [ 56 ].…”
Section: Disease Targets For Fetal and Neonatal Gene Therapymentioning
confidence: 99%
“…In a separate series of studies, self-complementary AAV8 containing human factor IX under the control of a synthetic liver-specific promoter was shown to establish prolonged high levels of gene expression when administered to mice and non-human primates [ 55 ]. This vector has been applied recently in a clinical trial where expression in one patient has risen from baseline to 1.5-2% and has maintained this level for more than 5 months [ 56 ].…”
Section: Disease Targets For Fetal and Neonatal Gene Therapymentioning
confidence: 99%
“…To generate a more efficient AAV vector, Nathwani and colleagues introduced three modifications to the original vector; these included switching to serotype 8, which has a tropism for liver [55]; use of a self‐complementary vector design, which obviates the need for second strand synthesis and leads to more efficient expression [56]; and use of a codon‐optimised vector to enhance translational efficiency [57]. This trial commenced in London in March 2010 and as presented at the American Society of Hematology meetings in December 2010, has led to long‐term expression of F.IX in two of the first four subjects infused [58]. After vector infusion it was subsequently shown that the two subjects who failed to express initially had low titre neutralising antibodies to AAV8 that had not been detected on the initial (less sensitive) screening assay.…”
Section: On‐going Trials Of Gene Therapy For Haemophilia B: Results Ementioning
confidence: 99%
“…The success of gene therapy in the preclinical haemophilia arena has been accruing for >15 years and proof of principle that gene therapy works in humans has been established in clinical trials (Murphy & High, 2008; Batorova et al , 2010). Currently, two Phase I/II trials are in progress with liver‐directed adeno‐associated virus (AAV) FIX gene transfer in which two different AAV serotypes are being evaluated (Murphy & High, 2008; Nathwani, 2010a; Nathwani et al , 2010b). These studies follow on from two previous AAV clinical trials in which the major obstacle to clinical benefit appears to have been the host immune response to the vector (Murphy & High, 2008; Batorova et al , 2010; Lillicrap, 2010).…”
Section: Novel Therapiesmentioning
confidence: 99%